RELASI HIJRAH DAN TAUBAT PERSPEKTIF HASBI ASH-SHIDDIEQY DALAM TAFSIR AL-NŪR - Iwan Gunawan (Tanzil: Jurnal Studi Al-Quran, 2022)
This research is motivated by the blurring of the meaning of the term hijrah among the people, especially in Indonesia. Of course, this is marked by the spread of some public figures who claim to have emigrated only by changing their appearance or fashion. Then it is used as a trend, even a business in a certain fashion, for example in terms of veils, clothes, and other things. This research uses a descriptive-analytic method in examining the theme of this discussion. The results of this study indicate that Hasbi Ash-Shiddieqy in his commentary argues that hijrah and repentance have a ‘umm wa khusūs muṭlaq relationship, namely every repentance is a migration, but not every hijrah is repentance. That hijrah has two dimensions of meaning, namely the physical meaning and the inner meaning. Physically, hijrah is a movement from one place to another solely because of Allah Swt. Whereas inwardly, hijrah is a change in a person from bad to good. While repentance according to him is returning to Allah Swt. or the return of the servant to goodness from what was originally in a state that is considered sinful